Investigação dos processos patológicos em elementos estruturais da Sede Administrativa da Cruz Vermelha do Amazonas - Benezar, Etlen Neves (Brasil, 2021)
Considering the current context of civil construction, it is clear that studies in search of more efficient construction systems have gained prominence. Therefore, the improvement of research collaborates to reduce the incidence of some factors that degrade structures, since the emergence of pathological processes in structural and constructive elements are increasingly common. Thus, this work observed the structural conditions of the administrative building of the Brazilian Red Cross of Amazonas and identified the degradations present in the structural system. From that, the pathological manifestations recognized during the visual inspections were registered through images and mapped according to the location of the structural parts of the building. After that, the test responsible for verifying the possibility of the existence of the carbonation process in the studied building structure was carried out, through the application of the phenolphthalein test. Finally, the study exposed the results regarding the deterioration conditions verified in the building, which can compromise the durability and safety of the enterprise, exposing the need for recovery procedures.